PERKAWINAN BEDA AGAMA PERSPEKTIF MAJELIS ULAMA INDONESIA - Basit Misbachul Fitri, Abdul; Sholeh, Moh. Badrus (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2022)
Indonesia is a plural country, the people have different religions. This is in accordance with Article 29 paragraph 2: